Habituation of 10-year-old hockey players to treadmill skating - Lockwood, K. L.; Frost, G. (Sports Biomechanics, 2007)
This study assessed changes in selected physiological and kinematic variables over 6 weeks of treadmill skating in an effort to understand the process of habituation to this novel training modality. Seven male, Atom-A hockey players who were injury-free and had no previous treadmill skating experience participated in the study. Players performed four 1-min skating bouts at progressively increasing speeds, each week, for 6 weeks. One speed (10.5 km/h) was repeated weekly to allow for assessment of the habituation process. Our criteria for habituation were: a decrease in stride rate, heart rate and rating of perceived exertion, and an increase in stride length, trunk angle and vertical movement of the centre of mass, leading to a plateau, over the course of the 6-week study. Significant decreases were seen in stride rate, heart rate and ratings of perceived exertion, and significant increases were found in stride length. Some of these changes were evident after only one week of training and all were present by week 4. After 6 weeks (24 min) of exposure to treadmill skating, all participants displayed a visibly more efficient skating style.